Pendapatan Asli Daerah, Dana Alokasi Umum Dan Belanja Modal - Devera Ch. N. Sapulete; Agustinus Salle; Novalia Herlina Bleskadit (Jurnal Akuntansi dan Keuangan Daerah, 2022)
This study aims to determine the effect of Regional Native Income (PAD) and General Allocation Fund (DAU) on Capital Expenditure in Regencies/Cities in Papua and West Papua Provinces. The population in this study is all regencies and cities in Papua and West Papua Provinces in 2019-2020. Data collection techniques use documentation methods. which was obtained directly from the official website of the Director General of Regional Financial Balance for the fiscal year 2019-2020 through the www.djpk.kemenkeu.go.id. The data analysis method used in this study is Multiple Regression Analysis with the help of SPSS 21. The results showed that partially regional original income had a positive effect on Capital Expenditure, but not significantly, the General Allocation Fund, had a positive and significant effect on Capital Expenditure and simultaneously PAD and DAU had a positive but not significant effect on Capital Expenditure.